2017
DOI: 10.1021/acs.jpcc.7b06617
|View full text |Cite
|
Sign up to set email alerts
|

Iron Intercalation in Covalent–Organic Frameworks: A Promising Approach for Semiconductors

Abstract: Covalent-organic frameworks (COFs) are intriguing platforms for designing functional molecular materials. Here, we present a computational study based on van der Waals dispersion-corrected hybrid density functional theory (DFT-D) to design boroxine-linked and triazine-linked COFs intercalated with Fe. Keeping the original P − 6m2 symmetry of the pristine COF (COF-Fe-0), we have computationally designed seven new COFs by intercalating Fe atoms between two organic layers. The equilibrium structures and electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 39 publications
1
74
0
Order By: Relevance
“…First-principle based hybrid density functional theory (DFT) was used to perform all the computations. [29][30][31][32][33] It is essential to include the long-range dispersion correction in the hybrid DFT [30][31][32][33][34][35][36][37][38][39][40][41][42] to describe the systems properly, as there are many weak van der Waals interactions in MOF model systems. The improved version of semi-empirical Grimme-D3 (ref.…”
Section: Computational Details and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…First-principle based hybrid density functional theory (DFT) was used to perform all the computations. [29][30][31][32][33] It is essential to include the long-range dispersion correction in the hybrid DFT [30][31][32][33][34][35][36][37][38][39][40][41][42] to describe the systems properly, as there are many weak van der Waals interactions in MOF model systems. The improved version of semi-empirical Grimme-D3 (ref.…”
Section: Computational Details and Methodologymentioning
confidence: 99%
“…The DFT and DFT-D methods were used for geometry optimization because densities and energies obtained with the methods are less affected by spin contamination than other approaches. [31][32][33][34][35][36][45][46][47][48] As stated earlier, Grimme and co-workers [37][38][39] introduced an improved version of the semi-empirical hybrid DFT method, DFT-D3, 38,40 which incorporates an additional term in the represented by the white, grey, dark yellow, red, and blackish red colours respectively, and S1, S2, and S3 are the imaginary planes. [37][38][39] demonstrated that using the DFT-D method with the z quality basis sets much of the basis set superposition error (BSSE) calculation is avoided, [37][38][39][48][49][50] which is otherwise essential for highly correlated methods like MP2 and coupled-cluster single double (triple) (CCSD(T)) methods.…”
Section: Computational Details and Methodologymentioning
confidence: 99%
“…[38] At present, a lot of COFs with the properties of low mass density, good crystallinity, high porosity, excellent chemical stability and high surface areas, have been explored in extensive potential applications by researchers. [39][40][41][42] So far, COFs have been applied in the fields of gas storage and separation, [43][44][45][46][47] heterogeneous catalysis, [48][49][50][51][52][53] sensors, [54][55][56][57][58][59] semiconductors, [60][61][62] drug delivery, [63][64][65][66] photoconduction [67,68] and especially energy storage. [69][70][71][72] In this paper, we focus on the major development of COFs as electrode materials for supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…17 COFs are lightweight, constructed by linking light elements such as carbon, boron, oxygen and silicon through exclusively strong covalent bonds that form periodic frameworks with the faces and edges of molecular subunits exposed to pores. 1,8,9 An attractive feature of some COFs is the high density of Lewis acidic boron atoms, present in boroxine (B 3 O 3 ) or boronate ester (C 2 O 2 B) rings, which are an integral component of their frameworks. Due to their high structural regularity and diversity, high surface areas, easy modication of frameworks, unique properties of porosity, and structural exibility, these COF materials have attracted considerable scientic interest for potential applications in gas storage/separation, 1014 photocatalysis, 15,16 solid state batteries, 17 optoelectronics 18 and even photovoltaics for fuel cells.…”
Section: Introductionmentioning
confidence: 99%